2008
DOI: 10.1063/1.3001934
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of the structural change generated by dielectric breakdown in MgO based magnetic tunnel junctions

Abstract: MgO based magnetic tunnel junctions are prepared to investigate the dielectric breakdown of the tunnel barrier. The breakdown is directly visualized by transmission electron microscopy measurements. The broken tunnel junctions are prepared for the microscopy measurements by focussed ion beam out of the junctions characterized by transport investigations. Consequently, a direct comparison of transport behavior and structure of the intact and broken junctions is obtained. Compared to earlier findings in Alumina … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…However, the morphology of the layers changes due to the voltage stress applied to the MTJ, e.g. the CoFeB can change from an amorphous to a crystalline structure and the interfaces between the thin films can be destroyed 37 . Therefore, this method allows only an estimation for the background thermovoltages arising from other sources of the layer stack of the tunnel junction that do not contribute to the TMS itself.…”
Section: Experiments On Magnesium Oxide and Silicon Substrates Amentioning
confidence: 99%
“…However, the morphology of the layers changes due to the voltage stress applied to the MTJ, e.g. the CoFeB can change from an amorphous to a crystalline structure and the interfaces between the thin films can be destroyed 37 . Therefore, this method allows only an estimation for the background thermovoltages arising from other sources of the layer stack of the tunnel junction that do not contribute to the TMS itself.…”
Section: Experiments On Magnesium Oxide and Silicon Substrates Amentioning
confidence: 99%
“…Baker et al 14 15 reported a rapid decrease in the damping due to reduced spin pumping with the addition of an ultra-thin MgO barrier layer between Fe and Pt, from which it was concluded that spin current can tunnel through a few monolayers of an insulating oxide barrier. The work was supported by transmission electron microscopy (TEM) imaging, which is limited to sampling very small areas and provides a projection of a thin 3D sample volume that may not show pinhole defects, and any defects present may be difficult to directly image 16 .…”
mentioning
confidence: 99%
“…We swept the voltage from zero to −600 to 600 mV and back to zero. Voltages of more than 600 mV led to a dielectric breakdown of the junctions (Thomas et al, 2008 ; Schaefers et al, 2009 ). All measurements are done with the bottom electrode as the reference potential.…”
Section: Resultsmentioning
confidence: 99%
“…These values are close to the dielectric breakdown voltage of the devices. Transmission electron microscopy images of MgO junctions before and after the dielectric breakdown are presented in our previous work (Thomas et al, 2008 ; Schaefers et al, 2009 ). Consequently, the investigations utilizing sequences of voltage pulses were limited to a maximum voltage of 500 mV.…”
Section: Methodsmentioning
confidence: 98%